Lived experiences of undergraduate medical students after failure in final professional examination—a phenomenology - Farrukh, Khadija; Usmani, Ambreen (Journal of the Pakistan Medical Association, 2023)
The objective of the study is to focuses on the actual phenomenon of medical students’ exposure to failure. The research aims to focus on the lived experiences of undergraduate medical students after failure in final professional examination, from the student’s point of view. Study was conducted in Bahria Medical and dental college Karachi, Pakistan. Interpretative phenomenological approach was used to explore the lived experiences of students who failed in the final professional MBBS examination. Interpretivist and pragmatic research paradigms were used for philosophical explanation of the phenomenon. Semi-structured interviews were conducted for data collection. These interviews were repeated until data saturation was reached. Interviews of participants were initially audio-recorded and then transcribed. Non-verbal communication was transcribed using observation method and following continuum of lexicalisation ranging from symbolic gestures to phrases or words omitted or adapted to enhance thick description and interpretation of latent content analysis. ---Continue